Security-Development Nexus and the Discourse of Fragile States - Anam, Syaiful (Jurnal Hubungan Internasional, 2013)
This paper will examine the underlying problem within the discourse of fragile state. It will be investigating the framework of security-development nexus used to justify the policy agenda of state and nation building in fragile states. It argues that the security development nexus underpinning the project of nation/state-building in âfragile statesâ obviously create insecurity and (re)produce inequality and poverty, rather than generate security and equality throughout society.